Experimental investigation of jet-induced resuspension of indoor deposited particles. Issue 3 (3rd March 2016) - Mei, Xiong; Zhang, Tengfei; Wang, Shugang
ABSTRACT: Particles deposited on indoor surfaces may be resuspended and become airborne when disturbed by intensive jets. Depending on the intended purpose, the resuspension of deposited particles may be minimized or promoted. This investigation experimentally measured the resuspension of Arizona test dusts (ATDs) after a jet impingement. The simulating pulsed jets were created by a tube using compressed nitrogen gas. The jets were released into the test section in a wind tunnel that was cleaned by high-efficiency particulate air (HEPA) filters. The particle resuspension was evaluated by the dust-removal zone shapes on particle-laden plates, total dust-removal mass, and the number of airborne particles. The effects of the jet impingement heights, surface dust loads, and particle-laden plate surface roughness on particle resuspension were examined. This study revealed that sparsely deposited dusts indoors are more difficult to resuspend by jets than are densely deposited dusts. The jet impingement to a surface whose roughness is comparable to the particle diameters may cause severer airborne particle exposure than to surfaces with extremely small or large roughness values. For a high surface dust load, there is an optimal jet impingement height that can resuspend the maximum amount of the deposited dusts. Copyright © 2016 American Association for Aerosol Research